Patagonia: Water and Built Habitat - Lolich, Liliana (2015)
This papes is about the vernacular architecture and other early constructions of the human habitat of Patagonia in Argentine. Most of them were made of wood, specially on the Andes forest. There were an important relation with the use of water not only for drinking, also for transportation. The principal objetive was to make a synthesis of many original studies in the region made along few years. It also contains comparative cases from de south of Chile. The methodology applied was descriptive and comparative analysis, using tables, pictures and architectural plans. Some conclusions are that over time, these testimonies of regional history are among the most representative components of touristic cultural landscape of the whole area.